Pengaruh Variasi Konsentrasi Starter Dan Lama Fermentasi Terhadap Kualitas Dan Total Keasaman Yoghurt Sari Biji Sirsak Dengan Pewarna Alami Sari Kulit Buah Manggis - Liyana, Dwi Anik; , Dra. Suparti, M.Si (2015)
Yogurt is a product processed from milk fermented by lactic bacteria. The content of seeds of soursop is acetogenis compounds, compounds acetogenis can kill cancer cells selectively and mangosteen rind menggadung anthosianin pigment that can be used as natural dyes in food. This study aims to determine the effect of variations in the concentration and length of fermentation starter to quality and total acidity yogurt soursop seed extract with natural dyes mangosteen rind. This study used a completely randomized design (CRD) with 2 factors and 3 replications. The first factor is the variation of the concentration which consists of 3 levels: 4%, 6%, 8%. Factor II is a long fermentation which consists of 3 levels: 19 hours, 21 hours, 23 hours. The results of this study indicate that variations in the concentration and length of fermentation starter affect the quality of seed soursop juice yoghurt, while variasri starter berpenaruh to the total acidity of yogurt seed soursop juice and fermentation time does not affect the total acidity yogurt seed extract with natural dyes soursop juice mangosteen fruit porters. P2R3 (starter 6% and fermentation time 19 hours) is a seed soursop juice yogurt is best according to the panelists because it has a thick texture, slightly brown color, distinctive aroma of yogurt, sour taste ,, and acceptance of love, while P3R1 treatment that produces a mean total acidity highest of 0.274%.